Coated electrode active material particles for lithium ion battery, electrode for lithium ion battery, and lithium ion battery
Coated electrode active material particles with a polymer compound, conductive filler, and organic solvent coating enhance lithium ion battery electrode flexibility and reduce internal resistance, addressing strength and capacity retention issues.
Patent Information
- Application Number
- JP2023096893
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-13
- Publication Date
- 2024-12-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing lithium ion battery electrodes face issues with electrode strength, flexibility, cycle characteristics, and rate characteristics, particularly in terms of capacity increase and internal resistance value.
Coated electrode active material particles for lithium ion batteries are developed, featuring a coating layer composed of a polymer compound, a conductive filler, and an organic solvent, with a specific weight ratio of the organic solvent, enhancing electrode flexibility and suppressing internal resistance increase.
The coated particles result in lithium ion batteries with improved electrode flexibility, reduced internal resistance, and enhanced capacity retention rates.
Smart Images

Figure 2024178619000001 
Figure 2024178619000002 
Figure 2024178619000003
Abstract
Description
[Technical field]
[0001] The present invention relates to coated electrode active material particles for lithium ion batteries, an electrode for lithium ion batteries, and a lithium ion battery. [Background technology]
[0002] Lithium ion batteries have come to be widely used in recent years for a variety of purposes as secondary batteries capable of achieving high energy density and high power density.
[0003] For example, Patent Document 1 discloses a resin composition for coating an active material of a non-aqueous secondary battery, the resin composition comprising a polymer of a monomer composition comprising an ester compound of a monohydric aliphatic alcohol having 1 to 12 carbon atoms with (meth)acrylic acid and an anionic monomer, the polymer having an acid value of 30 to 700; and a coated active material for a non-aqueous secondary battery, the coated active material having a coating layer comprising the resin composition for coating an active material on at least a part of the surface of the active material. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2017-160294 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, the resin composition for coating an active material disclosed in Patent Document 1 had room for improvement in terms of electrode strength (particularly electrode flexibility), cycle characteristics (increase in internal resistance value), and rate characteristics (capacity retention rate) when used in an electrode for a lithium ion battery or a lithium ion battery.
[0006] The present invention has been made in consideration of the above problems, and has an object to provide coated electrode active material particles for lithium ion batteries that can provide a lithium ion battery electrode and a lithium ion battery that have sufficient electrode flexibility, can suppress an increase in internal resistance value, and are excellent in capacity retention rate. [Means for solving the problem]
[0007] The present inventors conducted extensive research to solve the above problems and arrived at the present invention. The present invention provides coated electrode active material particles for lithium ion batteries, which are obtained by coating at least a part of the surface of electrode active material particles for lithium ion batteries with a coating layer containing a polymer compound, a conductive filler, and an organic solvent, wherein the weight ratio of the organic solvent contained in the coating layer is 10 to 1000 ppm based on the weight of the coated electrode active material particles for lithium ion batteries; an electrode for lithium ion batteries formed of a non-bound body containing the coated electrode active material particles for lithium ion batteries and a conductive assistant; and a lithium ion battery comprising the electrode for lithium ion batteries. Effect of the Invention
[0008] According to the present invention, it is possible to provide coated electrode active material particles for lithium ion batteries which have sufficient electrode flexibility, can suppress an increase in internal resistance value, and can provide a lithium ion battery electrode and a lithium ion battery having an excellent capacity retention rate.
[0009] <Coated electrode active material particles for lithium-ion batteries> The present invention relates to coated electrode active material particles for lithium ion batteries, in which at least a part of the surface of electrode active material particles for lithium ion batteries is coated with a coating layer containing a polymer compound, a conductive filler, and an organic solvent, and the weight ratio of the organic solvent contained in the coating layer is 10 to 1000 ppm based on the weight of the coated electrode active material particles for lithium ion batteries. In this specification, the term "lithium ion battery" is intended to include the concept of a lithium ion secondary battery.
[0010] In a lithium ion battery electrode (also simply referred to as an electrode) using the coated electrode active material particles for lithium ion batteries of the present invention, or in a lithium ion battery, a predetermined amount of organic solvent present in the coating layer of the coated electrode active material particles for lithium ion batteries improves the adhesive strength of the surface of the coated electrode active material particles for lithium ion batteries, and also causes electrolytic polymerization in the vicinity of the electrode active material particles during the initial charge to form an insulating coating, which is thought to suppress decomposition of the electrolyte, thereby improving the flexibility of the electrode, suppressing an increase in internal resistance, and improving the capacity retention rate.
[0011] (Electrode active material particles for lithium-ion batteries) The coated electrode active material particles for lithium ion batteries (also simply referred to as coated electrode active material particles) of the present invention are obtained by coating at least a portion of the surface of the electrode active material particles for lithium ion batteries with a coating layer containing a polymer compound, a conductive filler, and an organic solvent. First, the electrode active material particles for lithium ion batteries (also simply referred to as electrode active material particles) will be described in detail.
[0012] The electrode active material particles may be positive electrode active material particles for lithium ion batteries (also simply referred to as positive electrode active material particles) or negative electrode active material particles for lithium ion batteries (also simply referred to as negative electrode active material particles).
[0013] Positive electrode active material particles include composite oxides of lithium and transition metals {composite oxides containing one type of transition metal element (LiCoO2, LiNiO2, LiAlMnO4, LiMnO2, LiMn2O4, etc.), composite oxides containing two types of transition metal elements (e.g. LiFeMnO4, LiNi 1-x Co x O2, LiMn 1-y Co y O2, LiNi 1 / 3 Co 1 / 3 Al 1 / 3 O2 and LiNi 0.8 Co 0.15 Al0.05 O2) and composite oxides containing three or more transition metal elements [e.g. LiM a M' b M'' c O2(M, M' and M'' are different transition metal elements and satisfy a+b+c=1. For example, LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 Examples of the conductive polymer include lithium-containing transition metal phosphates (e.g., LiFePO4, LiCoPO4, LiMnPO4, and LiNiPO4), transition metal oxides (e.g., MnO2 and V2O5), transition metal sulfides (e.g., MoS2 and TiS2), and conductive polymers (e.g., polyaniline, polypyrrole, polythiophene, polyacetylene, poly-p-phenylene, and polyvinylcarbazole), and two or more of these may be used in combination. The lithium-containing transition metal phosphate may have some of the transition metal sites substituted with other transition metals.
[0014] From the viewpoint of the electrical characteristics of the battery, the positive electrode active material particles preferably have a volume average particle diameter of 0.01 to 100 μm, more preferably 0.1 to 35 μm, and even more preferably 2 to 30 μm. In this specification, the volume average particle size refers to the particle size (Dv50) at an integrated value of 50% in the particle size distribution determined by the Microtrack method (laser diffraction / scattering method). The Microtrack method is a method for determining the particle size distribution by utilizing scattered light obtained by irradiating particles with laser light. The volume average particle size can be measured using a Microtrack manufactured by Nikkiso Co., Ltd.
[0015] Examples of the negative electrode active material particles include carbon-based materials [graphite, non-graphitizable carbon (hard carbon), amorphous carbon, resin baked bodies (e.g., phenolic resins and furan resins baked and carbonized, etc.), cokes (e.g., pitch coke, needle coke, and petroleum coke, etc.), and carbon fibers, etc.], silicon-based materials [silicon, silicon oxide (SiO x), silicon-carbon composites (carbon particles whose surfaces are coated with silicon and / or silicon carbide, silicon particles or silicon oxide particles whose surfaces are coated with carbon and / or silicon carbide, and silicon carbide, etc.) and silicon alloys (silicon-aluminum alloy, silicon-lithium alloy, silicon-nickel alloy, silicon-iron alloy, silicon-titanium alloy, silicon-manganese alloy, silicon-copper alloy, silicon-tin alloy, etc.), conductive polymers (e.g. polyacetylene, polypyrrole, etc.), metals (tin, aluminum, zirconium, titanium, etc.), metal oxides (titanium oxide, lithium-titanium oxide, etc.) and metal alloys (e.g. lithium-tin alloy, lithium-aluminum alloy, lithium-aluminum-manganese alloy, etc.), and mixtures of these with carbon-based materials.
[0016] From the viewpoint of increasing the electric capacity, the negative electrode active material particles are preferably made of non-graphitizable carbon or a mixture of non-graphitizable carbon and a silicon-based material.
[0017] From the viewpoint of the electrical characteristics of the battery, the negative electrode active material particles preferably have a volume average particle size of 0.01 to 100 μm, more preferably 0.1 to 60 μm, and even more preferably 2 to 40 μm.
[0018] The weight proportion of the electrode active material particles is preferably 75 to 90% by weight, and more preferably 78.0 to 80.0% by weight, based on the weight of the coated electrode active material particles.
[0019] (polymer compound) The coating layer contains a polymer compound, a conductive filler, and an organic solvent. The coating layer may be a single-layer structure, or may be a two-layer structure consisting of a first coating layer that covers at least a portion of the surface of the electrode active material particles, and a second coating layer that covers at least a portion of the surface of the first coating layer. Whether the covering layer has a one-layer structure or a two-layer structure, the materials described below in relation to the polymer compound and conductive filler can be appropriately selected and used. The polymer compound will be described in detail below.
[0020] The polymer compound is preferably, for example, a resin containing a polymer having an acrylic monomer (a) as an essential constituent monomer. Specifically, the polymer compound constituting the coating layer is preferably a polymer of a monomer composition containing acrylic acid (a0) as the acrylic monomer (a). In the monomer composition, the content of acrylic acid (a0) is preferably more than 90% by weight and not more than 98% by weight based on the weight of the entire monomers. From the viewpoint of flexibility of the coating layer, the content of acrylic acid (a0) is more preferably 93.0 to 97.5% by weight, and even more preferably 95.0 to 97.0% by weight, based on the weight of the entire monomers.
[0021] The polymer compound constituting the coating layer may contain, as the acrylic monomer (a), a monomer (a1) having a carboxyl group or an acid anhydride group other than acrylic acid (a0).
[0022] Examples of the monomer (a1) having a carboxyl group or an acid anhydride group other than acrylic acid (a0) include monocarboxylic acids having 3 to 15 carbon atoms, such as methacrylic acid, crotonic acid, and cinnamic acid; dicarboxylic acids having 4 to 24 carbon atoms, such as maleic acid (anhydride), fumaric acid, itaconic acid (anhydride), citraconic acid, and mesaconic acid; and polycarboxylic acids having 6 to 24 carbon atoms and having a valence of 3 to 4 or more, such as aconitic acid.
[0023] The polymer compound constituting the coating layer may contain, as the acrylic monomer (a), a monomer (a2) represented by the following general formula (1). CH2=C(R 1 )COOR 2 (1) [In formula (1), R 1 is a hydrogen atom or a methyl group, R 2 is a linear alkyl group having 4 to 12 carbon atoms or a branched alkyl group having 3 to 36 carbon atoms.]
[0024] In the monomer (a2) represented by the above general formula (1), R 1R represents a hydrogen atom or a methyl group. 1 is preferably a methyl group. R 2 is preferably a linear or branched alkyl group having 4 to 12 carbon atoms, or a branched alkyl group having 13 to 36 carbon atoms.
[0025] (a21)R 2 is a linear or branched alkyl group having 4 to 12 carbon atoms Examples of the linear alkyl group having 4 to 12 carbon atoms include a butyl group, a pentyl group, a hexyl group, a heptyl group, an octyl group, a nonyl group, a decyl group, an undecyl group, and a dodecyl group. Examples of branched alkyl groups having 4 to 12 carbon atoms include 1-methylpropyl group (sec-butyl group), 2-methylpropyl group, 1,1-dimethylethyl group (tert-butyl group), 1-methylbutyl group, 1,1-dimethylpropyl group, 1,2-dimethylpropyl group, 2,2-dimethylpropyl group (neopentyl group), 1-methylpentyl group, 2-methylpentyl group, 3-methylpentyl group, 4-methylpentyl group, 1,1-dimethylbutyl group, 1,2-dimethylbutyl group, 1,3-dimethylbutyl group, and 2,2-dimethylbutyl group. , 2,3-dimethylbutyl, 1-ethylbutyl, 2-ethylbutyl, 1-methylhexyl, 2-methylhexyl, 3-methylhexyl, 4-methylhexyl, 5-methylhexyl, 1-ethylpentyl, 2-ethylpentyl, 3-ethylpentyl, 1,1-dimethylpentyl, 1,2-dimethylpentyl, 1,3-dimethylpentyl, 2,2-dimethylpentyl, 2,3-dimethylpentyl, 1-methylheptyl, 2-methylheptyl, 3-methylheptyl, 4-methylheptyl ethyl, 5-methylheptyl, 6-methylheptyl, 1,1-dimethylhexyl, 1,2-dimethylhexyl, 1,3-dimethylhexyl, 1,4-dimethylhexyl, 1,5-dimethylhexyl, 1-ethylhexyl, 2-ethylhexyl, 1-methyloctyl, 2-methyloctyl, 3-methyloctyl, 4-methyloctyl, 5-methyloctyl, 6-methyloctyl, 7-methyloctyl, 1,1-dimethylheptyl, 1,2-dimethylheptyl, 1,3-dimethylheptyl dimethylnonyl group, 1,4-dimethylheptyl group, 1,5-dimethylheptyl group, 1,6-dimethylheptyl group, 1-ethylheptyl group, 2-ethylheptyl group, 1-methylnonyl group, 2-methylnonyl group, 3-methylnonyl group, 4-methylnonyl group, 5-methylnonyl group, 6-methylnonyl group, 7-methylnonyl group, 8-methylnonyl group, 1,1-dimethyloctyl group, 1,2-dimethyloctyl group, 1,3-dimethyloctyl group, 1,4-dimethyloctyl group, 1,5-dimethyloctyl group, 1,6-dimethyloctyl group, 1,7-dimethyloctyl group, 1-ethyloctyl group, 2-ethyloctyl group, 1-methyldecyl group, 2-methyldecyl group, 3-methyldecyl group, 4-methyldecyl group, 5-methyldecyl group, 6-methyldecyl group, 7-methyldecyl group, 8-methyldecyl group, 9-methyldecyl group, 1,1-dimethylnonyl group, 1,2-dimethylnonyl group, 1,3-dimethylnonyl group, 1,4-dimethylnonyl group, 1,5-dimethylnonyl group, 1,6-dimethylnonyl group, 1,7-dimethylnonyl group, 1,8-dimethylnonyl group, 1-ethylnonyl group, 2-ethylnonyl group, 1-methylundecyl group, Examples of the dimethyldecyl group include 2-methylundecyl group, 3-methylundecyl group, 4-methylundecyl group, 5-methylundecyl group, 6-methylundecyl group, 7-methylundecyl group, 8-methylundecyl group, 9-methylundecyl group, 10-methylundecyl group, 1,1-dimethyldecyl group, 1,2-dimethyldecyl group, 1,3-dimethyldecyl group, 1,4-dimethyldecyl group, 1,5-dimethyldecyl group, 1,6-dimethyldecyl group, 1,7-dimethyldecyl group, 1,8-dimethyldecyl group, 1,9-dimethyldecyl group, 1-ethyldecyl group, and 2-ethyldecyl group. Among these, 2-ethyldecyl group is particularly preferred.
[0026] (a22)R 2 is a branched alkyl group having 13 to 36 carbon atoms Examples of branched alkyl groups having 13 to 36 carbon atoms include 1-alkylalkyl groups [1-methyldodecyl group, 1-butyleicosyl group, 1-hexyloctadecyl group, 1-octylhexadecyl group, 1-decyltetradecyl group, 1-undecyltridecyl group, etc.], 2-alkylalkyl groups [2-methyldodecyl group, 2-hexyloctadecyl group, 2-octylhexadecyl group, 2-decyltetradecyl group, 2-undecyltridecyl group, 2-dodecylhexadecyl group, 2-tridecylpentadecyl group, 2-decyloctadecyl group, 2-tetradecyloctadecyl group, 2-hexadecyloctadecyl group, 2-tetradecyloctadecyl group, 2-tetradecyleicosyl group, group, 2-hexadecyl eicosyl group, etc.), 3-34-alkylalkyl groups (3-alkylalkyl group, 4-alkylalkyl group, 5-alkylalkyl group, 32-alkylalkyl group, 33-alkylalkyl group, 34-alkylalkyl group, etc.), and mixed alkyl groups containing one or more branched alkyl groups such as a residue obtained by removing a hydroxyl group from an oxoalcohol obtained from a propylene oligomer (7-11-mer), an ethylene / propylene (molar ratio 16 / 1 to 1 / 11) oligomer, an isobutylene oligomer (7-8-mer), an α-olefin (carbon number 5-10) oligomer (4-8-mer), etc.
[0027] The polymer compound constituting the coating layer may contain, as the acrylic monomer (a), an ester compound (a3) of a monohydric aliphatic alcohol having 1 to 3 carbon atoms and (meth)acrylic acid. Examples of the monohydric aliphatic alcohol having 1 to 3 carbon atoms constituting the ester compound (a3) include methanol, ethanol, 1-propanol, and 2-propanol. Incidentally, (meth)acrylic acid means acrylic acid or methacrylic acid.
[0028] The polymer compound constituting the coating layer is preferably a polymer of a monomer composition containing acrylic acid (a0) and at least one of monomer (a1), monomer (a2) and ester compound (a3), more preferably a polymer of a monomer composition containing acrylic acid (a0) and at least one of monomer (a1), ester compound (a21) and ester compound (a3), still more preferably a polymer of a monomer composition containing acrylic acid (a0) and any one of monomer (a1), monomer (a2) and ester compound (a3), and most preferably a polymer of a monomer composition containing acrylic acid (a0) and any one of monomer (a1), ester compound (a21) and ester compound (a3). Examples of the polymer compound constituting the coating layer include a copolymer of acrylic acid and maleic acid using maleic acid as the monomer (a1), a copolymer of acrylic acid and 2-ethylhexyl methacrylate using 2-ethylhexyl methacrylate as the monomer (a2), and a copolymer of acrylic acid and methyl methacrylate using methyl methacrylate as the ester compound (a3).
[0029] From the viewpoint of suppressing the volume change of the electrode active material particles, the total content of the monomer (a1), the monomer (a2) and the ester compound (a3) is preferably 2.0 to 9.9% by weight, and more preferably 2.5 to 7.0% by weight, based on the total weight of the monomers.
[0030] It is preferable that the polymer compound constituting the coating layer does not contain, as the acrylic monomer (a), a salt of an anionic monomer having a polymerizable unsaturated double bond and an anionic group (a4).
[0031] Examples of the structure having a polymerizable unsaturated double bond include a vinyl group, an allyl group, a styrenyl group, and a (meth)acryloyl group. Examples of the anionic group include a sulfonic acid group and a carboxyl group. Anionic monomers having a polymerizable unsaturated double bond and an anionic group are compounds obtained by combining these, and examples thereof include vinyl sulfonic acid, allyl sulfonic acid, styrene sulfonic acid, and (meth)acrylic acid. The (meth)acryloyl group means an acryloyl group or a methacryloyl group. Examples of the cation constituting the salt of the anionic monomer (a4) include a lithium ion, a sodium ion, a potassium ion, and an ammonium ion.
[0032] In addition, the polymer compound constituting the coating layer may contain, as the acrylic monomer (a), a radically polymerizable monomer (a5) that is copolymerizable with the acrylic acid (a0), the monomer (a1), the monomer (a2), and the ester compound (a3), within a range that does not impair the physical properties. The radical polymerizable monomer (a5) is preferably a monomer not containing active hydrogen, and the following monomers (a51) to (a58) can be used.
[0033] (a51) A hydrocarbyl (meth)acrylate formed from at least one monol selected from the group consisting of a linear aliphatic monol having 13 to 20 carbon atoms, an alicyclic monol having 5 to 20 carbon atoms, and an aromatic aliphatic monol having 7 to 20 carbon atoms, and (meth)acrylic acid. Examples of the monool include (i) linear aliphatic monools (tridecyl alcohol, myristyl alcohol, pentadecyl alcohol, cetyl alcohol, heptadecyl alcohol, stearyl alcohol, nonadecyl alcohol, arachidyl alcohol, etc.), (ii) alicyclic monools (cyclopentyl alcohol, cyclohexyl alcohol, cycloheptyl alcohol, cyclooctyl alcohol, etc.), (iii) aromatic aliphatic monools (benzyl alcohol, etc.), and mixtures of two or more of these.
[0034] (a52) Poly(n=2-30) oxyalkylene (carbon number: 2-4) alkyl (carbon number: 1-18) ether (meth)acrylate [(meth)acrylate of 10 moles of ethylene oxide (hereinafter abbreviated as EO) adduct of methanol, (meth)acrylate of 10 moles of propylene oxide (hereinafter abbreviated as PO) adduct of methanol, etc.]
[0035] (a53) Nitrogen-containing vinyl compounds (a53-1) Amide group-containing vinyl compound (i) (meth)acrylamide compounds having 3 to 30 carbon atoms, such as N,N-dialkyl (having 1 to 6 carbon atoms) or diaralkyl (having 7 to 15 carbon atoms) (meth)acrylamides (N,N-dimethylacrylamide, N,N-dibenzylacrylamide, etc.), diacetone acrylamide (ii) Amido group-containing vinyl compounds having 4 to 20 carbon atoms, excluding the above (meth)acrylamide compounds, such as N-methyl-N-vinylacetamide and cyclic amides [pyrrolidone compounds (having 6 to 13 carbon atoms, such as N-vinylpyrrolidone)]
[0036] (a53-2) (Meth)acrylate compounds (i) Dialkyl (C1-4) aminoalkyl (C1-4) (meth)acrylates [N,N-dimethylaminoethyl (meth)acrylate, N,N-diethylaminoethyl (meth)acrylate, t-butylaminoethyl (meth)acrylate, morpholinoethyl (meth)acrylate, etc.] (ii) Quaternary ammonium group-containing (meth)acrylates {quaternized products of tertiary amino group-containing (meth)acrylates [N,N-dimethylaminoethyl (meth)acrylate, N,N-diethylaminoethyl (meth)acrylate, etc.] (those quaternized using a quaternizing agent such as methyl chloride, dimethyl sulfate, benzyl chloride, dimethyl carbonate, etc.)}
[0037] (a53-3) Heterocycle-containing vinyl compounds Pyridine compounds (having 7 to 14 carbon atoms, such as 2- or 4-vinylpyridine), imidazole compounds (having 5 to 12 carbon atoms, such as N-vinylimidazole), pyrrole compounds (having 6 to 13 carbon atoms, such as N-vinylpyrrole), pyrrolidone compounds (having 6 to 13 carbon atoms, such as N-vinyl-2-pyrrolidone)
[0038] (a53-4) Nitrile group-containing vinyl compounds Nitrile group-containing vinyl compounds having 3 to 15 carbon atoms, such as (meth)acrylonitrile, cyanostyrene, and cyanoalkyl (carbon number 1 to 4) acrylates
[0039] (A53-5) Other nitrogen-containing vinyl compounds Nitro group-containing vinyl compounds (carbon numbers 8 to 16, e.g., nitrostyrene), etc.
[0040] (a54) Vinyl hydrocarbons (A54-1) Aliphatic vinyl hydrocarbons Olefins with 2 to 18 carbon atoms or more (ethylene, propylene, butene, isobutylene, pentene, heptene, diisobutylene, octene, dodecene, octadecene, etc.), dienes with 4 to 10 carbon atoms or more (butadiene, isoprene, 1,4-pentadiene, 1,5-hexadiene, 1,7-octadiene, etc.), etc.
[0041] (A54-2) Alicyclic vinyl hydrocarbons Cyclic unsaturated compounds having 4 to 18 carbon atoms or more, such as cycloalkenes (e.g., cyclohexene), (di)cycloalkadienes [e.g., (di)cyclopentadiene], terpenes (e.g., pinene and limonene), indenes
[0042] (A54-3) Aromatic vinyl hydrocarbons Aromatic unsaturated compounds having 8 to 20 carbon atoms or more, such as styrene, α-methylstyrene, vinyltoluene, 2,4-dimethylstyrene, ethylstyrene, isopropylstyrene, butylstyrene, phenylstyrene, cyclohexylstyrene, and benzylstyrene.
[0043] (a55) Vinyl ester Aliphatic vinyl esters [having 4 to 15 carbon atoms, for example, alkenyl esters of aliphatic carboxylic acids (mono- or dicarboxylic acids) (for example, vinyl acetate, vinyl propionate, vinyl butyrate, diallyl adipate, isopropenyl acetate, vinyl methoxyacetate)] Aromatic vinyl esters [having 9 to 20 carbon atoms, for example, alkenyl esters of aromatic carboxylic acids (mono- or dicarboxylic acids) (for example, vinyl benzoate, diallyl phthalate, methyl-4-vinyl benzoate), aromatic ring-containing esters of aliphatic carboxylic acids (for example, acetoxystyrene)]
[0044] (a56) Vinyl ether Aliphatic vinyl ethers [C3-15, e.g., vinyl alkyl (C1-10) ethers (vinyl methyl ether, vinyl butyl ether, vinyl 2-ethylhexyl ether, etc.), vinyl alkoxy (C1-6) alkyl (C1-4) ethers (vinyl-2-methoxyethyl ether, methoxybutadiene, 3,4-dihydro-1,2-pyran, 2-butoxy-2'-vinyloxydiethyl ether, vinyl-2-ethylmercaptoethyl ether, etc.), poly(2-4)(meth)allyloxyalkanes (C2-6) (diallyloxyethane, triallyloxyethane, tetraallyloxybutane, tetramethallyloxyethane, etc.)], aromatic vinyl ethers (C8-20, e.g., vinyl phenyl ether, phenoxystyrene)
[0045] (a57) Vinyl ketone Aliphatic vinyl ketones (carbon numbers 4 to 25, e.g., vinyl methyl ketone, vinyl ethyl ketone), aromatic vinyl ketones (carbon numbers 9 to 21, e.g., vinyl phenyl ketone)
[0046] (a58) Unsaturated dicarboxylic acid diesters Unsaturated dicarboxylic acid diesters having 4 to 34 carbon atoms, such as dialkyl fumarate (wherein the two alkyl groups are linear, branched, or alicyclic groups having 1 to 22 carbon atoms), dialkyl maleate (wherein the two alkyl groups are linear, branched, or alicyclic groups having 1 to 22 carbon atoms).
[0047] When the radical polymerizable monomer (a5) is contained, the content thereof is preferably 0.1 to 3.0% by weight based on the weight of the total monomers.
[0048] The lower limit of the weight average molecular weight of the polymer compound constituting the coating layer is preferably 3,000, more preferably 5,000, and even more preferably 7,000. On the other hand, the upper limit of the weight average molecular weight of the polymer compound is preferably 100,000, and more preferably 70,000.
[0049] The weight average molecular weight of the polymer compound constituting the coating layer can be determined by gel permeation chromatography (hereinafter abbreviated as GPC) measurement under the following conditions. Apparatus: Alliance GPC V2000 (Waters) Solvent: orthodichlorobenzene, N-dimethylformamide (DMF), tetrahydrofuran (THF) Standard material: polystyrene Sample concentration: 3mg / ml Column stationary phase: PLgel 10 μm, MIXED-B 2 columns in series (Polymer Laboratories) Column temperature: 135℃
[0050] The polymer compound constituting the coating layer can be produced by a known polymerization method (bulk polymerization, solution polymerization, emulsion polymerization, suspension polymerization, etc.) using a known polymerization initiator {azo initiator [2,2'-azobis(2-methylpropionitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2-methylbutyronitrile), etc.], peroxide initiator (benzoyl peroxide, di-t-butyl peroxide, lauryl peroxide, etc.), etc.}. The amount of the polymerization initiator used is preferably 0.01 to 5% by weight, more preferably 0.05 to 2% by weight, and even more preferably 0.1 to 1.5% by weight based on the total weight of the monomers, from the viewpoint of adjusting the weight average molecular weight within a preferred range, and the polymerization temperature and polymerization time are adjusted depending on the type of polymerization initiator, etc., but the polymerization temperature is preferably -5 to 150°C (more preferably 30 to 120°C), and the reaction time is preferably 0.1 to 50 hours (more preferably 2 to 24 hours).
[0051] Examples of the solvent used in the case of solution polymerization include esters (having 2 to 8 carbon atoms, such as ethyl acetate and butyl acetate), alcohols (having 1 to 8 carbon atoms, such as methanol, ethanol, and octanol), hydrocarbons (having 4 to 8 carbon atoms, such as n-butane, cyclohexane, and toluene), amides (such as N,N-dimethylformamide (hereinafter abbreviated as DMF)), and ketones (having 3 to 9 carbon atoms, such as methyl ethyl ketone). From the viewpoint of adjusting the weight average molecular weight to a preferred range, the amount of the solvent used is preferably 5 to 900% by weight, more preferably 10 to 400% by weight, and even more preferably 30 to 300% by weight based on the total weight of the monomers, and the monomer concentration is preferably 10 to 95% by weight, more preferably 20 to 90% by weight, and even more preferably 30 to 80% by weight.
[0052] Examples of the dispersion medium in the emulsion polymerization and suspension polymerization include water, alcohol (e.g., ethanol), ester (e.g., ethyl propionate), light naphtha, etc., and examples of the emulsifier include metal salts of higher fatty acids (having 10 to 24 carbon atoms) (e.g., sodium oleate and sodium stearate), metal salts of higher alcohol (having 10 to 24 carbon atoms) sulfate (e.g., sodium lauryl sulfate), ethoxylated tetramethyldecynediol, sodium sulfoethyl methacrylate, dimethylaminomethyl methacrylate, etc. Furthermore, polyvinyl alcohol, polyvinylpyrrolidone, etc. may be added as a stabilizer. The monomer concentration in the solution or dispersion is preferably 5 to 95% by weight, more preferably 10 to 90% by weight, and even more preferably 15 to 85% by weight, and the amount of the polymerization initiator used is preferably 0.01 to 5% by weight, more preferably 0.05 to 2% by weight, based on the total weight of the monomers. In the polymerization, known chain transfer agents such as mercapto compounds (dodecyl mercaptan, n-butyl mercaptan, etc.) and / or halogenated hydrocarbons (carbon tetrachloride, carbon tetrabromide, benzyl chloride, etc.) can be used.
[0053] The polymer compound constituting the coating layer may be a crosslinked polymer obtained by crosslinking the polymer compound with a crosslinking agent (A') having a reactive functional group that reacts with a carboxyl group {preferably a polyepoxy compound (a'1) [polyglycidyl ether (bisphenol A diglycidyl ether, propylene glycol diglycidyl ether, glycerin triglycidyl ether, etc.) and polyglycidylamine (N,N-diglycidylaniline and 1,3-bis(N,N-diglycidylaminomethyl)) and the like] and / or a polyol compound (a'2) (ethylene glycol, etc.)}.
[0054] As a method of crosslinking the polymer compound constituting the coating layer using the crosslinking agent (A'), there is a method of crosslinking the electrode active material particles after coating them with the polymer compound constituting the coating layer.Specifically, there is a method of producing coated electrode active material particles by mixing the electrode active material particles with a resin solution containing the polymer compound constituting the coating layer and removing the solvent, and then mixing the coated electrode active material particles with a solution containing the crosslinking agent (A') and heating the mixture to cause desolvation and crosslinking reaction, and a reaction in which the polymer compound constituting the coating layer is crosslinked by the crosslinking agent (A') occurs on the surface of the electrode active material particles. The heating temperature is adjusted depending on the type of crosslinking agent, but is preferably 70°C or higher when a polyepoxy compound (a'1) is used as the crosslinking agent, and is preferably 120°C or higher when a polyol compound (a'2) is used.
[0055] The temperature in the system in the polymerization reaction is usually -5 to 150°C, and preferably 30 to 120°C, the reaction time is usually 0.1 to 50 hours, and preferably 2 to 24 hours, and the end point of the polymerization reaction is the point where the amount of unreacted monomer is usually 5 wt% or less, and preferably 1 wt% or less, based on the total weight of the monomer components contained in the monomer composition, and the amount of unreacted monomer can be confirmed by a known method for quantifying the monomer content, such as gas chromatography.
[0056] When the coating layer has a single layer configuration, the weight ratio of the polymer compound is preferably 0.3 to 10.0% by weight based on the weight of the coated electrode active material particles. When the coating layer has a two-layer structure, the weight proportion of the polymer compound contained in the first coating layer is preferably 0.7 to 9.0 wt % based on the weight of the coated electrode active material particles, and the weight proportion of the polymer compound contained in the second coating layer is preferably 0.3 to 9.0 wt % based on the weight of the coated electrode active material particles.
[0057] (Conductive filler) The conductive filler contained in the coating layer will be described in detail.
[0058] The conductive filler is preferably selected from materials having electrical conductivity. Preferred conductive fillers include metals [aluminum, stainless steel (SUS), silver, gold, copper, titanium, etc.], carbon [graphite and carbon black (acetylene black, ketjen black, furnace black, channel black, thermal lamp black, etc.)], and mixtures thereof. These conductive fillers may be used alone or in combination of two or more kinds, and may also be used as alloys or metal oxides thereof. Among these, from the viewpoint of electrical stability, aluminum, stainless steel, carbon, silver, gold, copper, titanium and mixtures thereof are more preferable, silver, gold, aluminum, stainless steel and carbon are further preferable, and carbon is particularly preferable. Furthermore, these conductive fillers may be formed by coating a particulate ceramic material or a resin material with a conductive material (preferably a metal one of the conductive fillers described above) by plating or the like.
[0059] The shape (form) of the conductive filler is not limited to a particulate form, and may be a form other than a particulate form, and may be a form that is in practical use as a so-called filler-based conductive filler, such as carbon nanofibers or carbon nanotubes.
[0060] The average particle size of the conductive filler is not particularly limited, but from the viewpoint of the electrical characteristics of the battery, it is preferably about 0.01 to 10 μm. In this specification, the "particle diameter of the conductive filler" refers to the maximum distance L between any two points on the contour line of the conductive filler. The value of the "average particle diameter" is calculated as the average particle diameter of 30 particles using an observation means such as a scanning electron microscope (SEM) or a transmission electron microscope (TEM).
[0061] When the coating layer has a single layer configuration, the weight proportion of the conductive filler is preferably 2 to 14% by weight, and more preferably 3 to 11% by weight, based on the weight of the coated electrode active material particles. Furthermore, when the coating layer has a two-layer structure, the weight proportion of the conductive filler contained in the first coating layer is preferably 3.0 to 8.0 wt % based on the weight of the coated electrode active material particles, and the weight proportion of the conductive filler contained in the second coating layer is more preferably 2.0 to 6.0 wt % based on the weight of the coated electrode active material particles. When the weight proportion of the conductive filler is within the above range, the secondary particles of the coated electrode active material particles are maintained, and a lithium ion battery electrode and a lithium ion battery having an excellent discharge capacity retention rate can be obtained.
[0062] The ratio of the polymer compound constituting the coating layer to the conductive filler is not particularly limited, whether the coating layer has a single layer structure or a two-layer structure. From the viewpoint of the discharge capacity maintenance rate of the battery, the weight ratio of the polymer compound (resin solid content weight) constituting the coating layer to the conductive filler is preferably 1:0.01 to 1:50, and more preferably 1:0.2 to 1:4.0.
[0063] (Organic solvent) The coating layer includes an organic solvent.
[0064] The organic solvent contained in the coating layer is not particularly limited as long as it is an organic solvent capable of dissolving the polymer compound, and the solvents exemplified as those used when producing the above-mentioned polymer compound by solution polymerization can be suitably used. The organic solvent contained in the coating layer may be an organic solvent (residual organic solvent) used during synthesis of the polymer compound, or an organic solvent added after the coating layer is formed.
[0065] From the viewpoint of flexibility of the resulting electrode, the organic solvent contained in the coating layer is preferably one or more selected from the group consisting of acetone, toluene, isopropyl alcohol, ethyl acetate, N,N-dimethylformamide, and N-methyl-2-pyrrolidone. Among these, N,N-dimethylformamide (DMF) is preferred from the viewpoint of ease of adjusting the content of the organic solvent in the coating layer.
[0066] The weight ratio of the organic solvent contained in the coating layer is 10 to 1000 ppm based on the weight of the coated electrode active material particles. By setting the weight ratio of the organic solvent contained in the coating layer within the above range, the flexibility of the electrode is improved, an increase in internal resistance can be suppressed, and a lithium ion battery electrode and a lithium ion battery having excellent capacity retention can be obtained.
[0067] The weight ratio of the organic solvent contained in the coating layer can be measured, for example, by the following method. A tetrahydrofuran solution is prepared using propylene glycol monomethyl ether as an internal standard substance, and a calibration curve solution is prepared by dissolving various monomers to be measured. The coated active material is dissolved in the above tetrahydrofuran solution at a 10-fold dilution and measured with a GC measurement device (Shimadzu Corporation: Gas Chromatograph GC-2010). The weight percentage of the organic solvent is calculated in ppm order from the area ratio of the peak intensity.
[0068] The weight ratio of the organic solvent contained in the coating layer is preferably 10 to 950 ppm, and more preferably 10 to 800 ppm, based on the weight of the coated electrode active material particles.
[0069] When the coating layer has a two-layer structure, the total weight ratio of the organic solvent contained in the first coating layer and the organic solvent contained in the second coating layer is 10 to 1000 ppm based on the weight of the coated electrode active material particles for lithium ion batteries. In this case, the weight ratio of the organic solvent contained in the first coating layer is preferably 5 to 500 ppm based on the weight of the coated electrode active material particles for lithium ion batteries. The weight ratio of the organic solvent contained in the second coating layer is preferably 5 to 500 ppm based on the weight of the coated electrode active material particles for lithium ion batteries.
[0070] (others) In the coated electrode active material particles for lithium ion batteries of the present invention, the coating layer may further contain ceramic particles. Examples of the ceramic particles include metal carbide particles, metal oxide particles, and glass ceramic particles.
[0071] Examples of metal carbide particles include silicon carbide (SiC), tungsten carbide (WC), molybdenum carbide (Mo2C), titanium carbide (TiC), tantalum carbide (TaC), niobium carbide (NbC), vanadium carbide (VC), and zirconium carbide (ZrC).
[0072] Examples of metal oxide particles include zinc oxide (ZnO), aluminum oxide (Al2O3), silicon dioxide (SiO2), tin oxide (SnO2), titania (TiO2), zirconia (ZrO2), indium oxide (In2O3), Li2B4O7, and Li4Ti5O. 12 , Li2Ti2O5, LiTaO3, LiNbO3, LiAlO2, Li2ZrO3, Li2WO4, Li2TiO3, Li3PO4, Li2MoO4, Li3BO3, LiBO2, Li2CO3, Li2SiO3, and perovskite-type oxide particles represented by ABO3 (wherein A is at least one selected from the group consisting of Ca, Sr, Ba, La, Pr, and Y, and B is at least one selected from the group consisting of Ni, Ti, V, Cr, Mn, Fe, Co, Mo, Ru, Rh, Pd, and Re). As the metal oxide particles, zinc oxide (ZnO), aluminum oxide (Al2O3), silicon dioxide (SiO2), and lithium tetraborate (Li2B4O7) are preferred from the viewpoint of suitably suppressing side reactions that occur between the electrolyte and the coated electrode active material particles.
[0073] The glass ceramic particles are preferably a lithium-containing phosphate compound having a rhombohedral crystal system, and the chemical formula is Li x M”2P3O 12 (X=1~1.7). Here, M" is one or more elements selected from the group consisting of Zr, Ti, Fe, Mn, Co, Cr, Ca, Mg, Sr, Y, Sc, Sn, La, Ge, Nb, and Al. In addition, a part of P may be replaced with Si or B, and a part of O may be replaced with F, Cl, etc. For example, Li 1.15 Ti 1.85 Al 0.15 S 0.05 P 2.95 O 12 , Li 1.2 Ti 1.8 Al 0.1 Ge 0.1 S 0.05 P 2.95 O 12 etc. can be used. Materials of different compositions may be mixed or composited, or the surface may be coated with a glass electrolyte, etc. Alternatively, it is preferable to use glass ceramic particles that precipitate a crystal phase of a lithium-containing phosphate compound having a NASICON structure by heat treatment. Examples of the glass electrolyte include the glass electrolyte described in JP-A-2019-96478.
[0074] The volume average particle size of the ceramic particles is preferably from 1 to 1000 nm, more preferably from 1 to 500 nm, and further preferably from 1 to 150 nm, from the viewpoints of energy density and electrical resistance value.
[0075] The weight proportion of the ceramic particles is preferably 0.5 to 5.0% by weight based on the weight of the coated electrode active material particles. By including the ceramic particles in the above range, side reactions occurring between the electrolyte and the coated electrode active material particles can be suppressed.
[0076] (Coverage rate) The coated electrode active material particles for lithium ion batteries of the present invention are obtained by coating at least a part of the surface of the electrode active material particles with a coating layer containing a polymer compound and a conductive filler.
[0077] When the coating layer has a single layer structure, from the viewpoint of cycle characteristics, the coating rate obtained by the following calculation formula is preferably 30 to 95%. Coverage rate (%) = {1 - [BET specific surface area of coated electrode active material particles / (BET specific surface area of electrode active material particles before coating × weight ratio of electrode active material particles contained in coated electrode active material particles + BET specific surface area of conductive filler × weight ratio of conductive filler contained in coated electrode active material particles + BET specific surface area of ceramic particles × weight ratio of ceramic particles contained in coated electrode active material particles)]} × 100
[0078] When the coating layer has a two-layer structure, the coverage of the first coating layer, calculated by the following formula, is preferably 30 to 95%, from the viewpoint of capacity retention. Coverage rate (%) = {1 - [BET specific surface area of electrode active material particles coated with first coating layer / (BET specific surface area of uncoated electrode active material particles × weight ratio of electrode active material particles contained in electrode active material particles coated with first coating layer + BET specific surface area of conductive filler × weight ratio of conductive filler contained in electrode active material particles coated with first coating layer + BET specific surface area of optionally contained ceramic particles × weight ratio of optionally contained ceramic particles in electrode active material particles coated with first coating layer)]} × 100
[0079] When the coating layer has a two-layer structure, it is preferable that at least a part of the surface of the first coating layer is coated with the second coating layer. From the viewpoint of electrode strength, the coverage of the second coating layer with respect to the first coating layer is preferably 30 to 95%. The coverage of the second coating layer can be obtained by calculation from the BET specific surface area of the sample after coating with the first coating layer and the BET specific surface area of the second coating layer. Coverage rate (%) = {1 - [BET specific surface area of electrode active material particles coated with the second coating layer / (BET specific surface area of electrode active material particles coated with the first coating layer × weight ratio of electrode active material particles contained in electrode active material particles coated with the second coating layer + BET specific surface area of conductive filler × weight ratio of conductive filler contained in electrode active material particles coated with the second coating layer + BET specific surface area of ceramic particles optionally contained × weight ratio of ceramic particles optionally contained in electrode active material particles coated with the second coating layer)]} × 100
[0080] When the coating layer has a two-layer structure, there may be a portion on the surface of the electrode active material particle where the first coating layer is not formed, and there may be a portion on the surface of the electrode active material particle where the second coating layer is formed.
[0081] <Method of manufacturing coated electrode active material particles for lithium ion batteries> The coated electrode active material particles for lithium ion batteries of the present invention can be produced by mixing the polymer compound constituting the coating layer, the conductive filler, and the electrode active material particles. The order in which the polymer compound, the conductive filler, and the electrode active material particles are mixed is not particularly limited. For example, a resin composition consisting of a polymer compound and a conductive filler that constitute a coating layer that have been mixed in advance may be further mixed with the electrode active material particles, the polymer compound, the conductive filler, and the electrode active material particles may be mixed simultaneously, or the polymer compound may be mixed with the electrode active material particles, and then the conductive filler may be mixed therewith.
[0082] The coated electrode active material particles of the present invention can be obtained by coating electrode active material particles with a polymer compound. For example, the electrode active material particles are placed in a universal mixer and stirred at 30 to 800 rpm, while a resin solution containing a polymer electrolyte composition is dropwise added and mixed over 1 to 90 minutes, a conductive filler is further mixed, the temperature is increased to 50 to 200°C while stirring, the pressure is reduced to 0.007 to 0.04 MPa, and the mixture is maintained for 10 to 900 minutes, and then an organic solvent is added so that the weight ratio of the organic solvent contained in the coated electrode active material particles falls within a predetermined range.
[0083] The compounding ratio of the electrode active material particles to the polymer compound and the conductive filler is not particularly limited, but it is preferable that the weight ratio of the electrode active material particles:total weight of the polymer compound and the conductive filler is 1:0.001 to 0.1.
[0084] When the coating layer has a two-layer structure, it is preferable to have a first coating step in which a coating layer composition for a first coating layer, which is a mixture of electrode active material particles, a polymer compound, an organic solvent, optionally a conductive filler, and optionally ceramic particles, is desolvated to obtain first coated electrode active material particles, and a second coating step in which a coating layer composition for a second coating layer, which is a mixture of the first coated electrode active material particles, a polymer compound, an organic solvent, optionally a conductive filler, and optionally ceramic particles, is desolvated. The monomer may be contained in either the coating layer composition for the first coating layer or the coating layer composition for the second coating layer, but is preferably contained in both. The method for removing the solvent from the coating layer composition for the first coating layer and the coating layer composition for the second coating layer may be the method described above.
[0085] <Electrodes for lithium-ion batteries> The lithium ion battery electrode of the present invention comprises a non-bound body containing the coated electrode active material particles for lithium ion batteries of the present invention and a conductive assistant. Here, the term "non-bound body" means that the coated electrode active material particles for lithium ion batteries and the conductive assistant are not fixed in position by a binding agent (also called a binder). That is, the coated electrode active material particles for lithium ion batteries and the conductive assistant are in a state in which they can move in response to an external force.
[0086] The lithium ion battery electrode of the present invention does not contain a solvent drying type binder. Examples of the solvent-drying binder include known binders for lithium ion batteries such as starch, polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, etc. These binders are used by dissolving or dispersing them in a solvent, and by volatilizing or distilling off the solvent, the surface becomes solidified without exhibiting adhesion, and firmly fixes the coated electrode active material particles and the conductive assistant to each other, and the coated electrode active material particles, the conductive assistant, and the current collector.
[0087] The lithium ion battery electrode of the present invention has sufficient electrode flexibility. Specifically, the yield stroke shown below is 0.13 mm or more. If the yield stroke is 0.13 mm or more, the lithium ion battery electrode can maintain its electrical conductivity even when it is stretched or distorted. The yield stroke is preferably 0.15 mm or more, and more preferably 0.17 mm or more.
[0088] In this specification, the yield stroke is measured and calculated by the following method. The yield stress of a lithium-ion battery electrode (sample size: 16 mm diameter circle) is measured using an autograph (manufactured by Shimadzu Corporation) in accordance with ISO178 (Plastics - Determination of bending properties). A sample of the lithium-ion battery electrode is set on a jig with a support distance of 5 mm, and a load cell (rated load: 20 N) set on an autograph is lowered toward the electrode at a rate of 1 mm / min. The distance (mm) that the load cell drops from when it touches the electrode to the yield point is calculated as the yield point stroke.
[0089] The lithium ion battery electrode of the present invention preferably comprises an electrode active material layer containing coated electrode active material particles, a conductive assistant, and an electrolytic solution containing an electrolyte and a solvent, and a current collector.
[0090] (Coated electrode active material particles) As the coated electrode active material particles, the coated electrode active material particles for lithium ion batteries of the present invention are used. Based on the weight of the electrode active material layer, the coated electrode active material particles are contained at preferably 40 to 95% by weight, and more preferably 60 to 90% by weight.
[0091] (Conductive assistant) The lithium ion battery electrode of the present invention contains a conductive assistant in addition to the conductive filler that may be contained in the coating layer of the coated electrode active material particles described above. It can be distinguished in that the conductive filler contained in the coating layer is integral with the coated electrode active material particles, whereas the conductive assistant is contained separately from the coated electrode active material particles.
[0092] The conductive assistant may be the same as or different from the conductive filler contained in the coating layer. As the conductive assistant contained in the lithium ion battery electrode of the present invention, the same materials as those exemplified as the conductive filler can be used.
[0093] The total content of the conductive assistant contained in the lithium ion battery electrode and the conductive filler contained in the coating layer is not particularly limited, but is preferably 0.5 to 20% by weight based on the weight of the electrode active material layer excluding the electrolyte.
[0094] (electrolyte) The electrolytic solution contains an electrolyte and a solvent.
[0095] As the electrolyte, electrolytes used in known electrolytic solutions can be used, for example, lithium salts of inorganic anions such as LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, and LiN(FSO2)2, and lithium salts of organic anions such as LiN(CF3SO2)2, LiN(C2F5SO2)2, and LiC(CF3SO2)3. Of these, LiN(FSO2)2 is preferred from the viewpoint of battery output and charge / discharge cycle characteristics.
[0096] As the solvent, a non-aqueous solvent used in a known electrolytic solution can be used, for example, a lactone compound, a cyclic or chain carbonate ester, a chain carboxylate ester, a cyclic or chain ether, a phosphate ester, a nitrile compound, an amide compound, a sulfone, a sulfolane, and a mixture thereof can be used.
[0097] Examples of the lactone compound include lactone compounds having a five-membered ring (such as γ-butyrolactone and γ-valerolactone) and a six-membered ring (such as δ-valerolactone).
[0098] Examples of the cyclic carbonate ester include propylene carbonate, ethylene carbonate (EC), and butylene carbonate (BC). Examples of the chain carbonate ester include dimethyl carbonate (DMC), methyl ethyl carbonate (MEC), diethyl carbonate (DEC), methyl-n-propyl carbonate, ethyl-n-propyl carbonate, and di-n-propyl carbonate.
[0099] Examples of the chain carboxylate include methyl acetate, ethyl acetate, propyl acetate, and methyl propionate.
[0100] Examples of cyclic ethers include tetrahydrofuran, tetrahydropyran, 1,3-dioxolane, and 1,4-dioxane. Examples of chain ethers include dimethoxymethane and 1,2-dimethoxyethane.
[0101] Examples of phosphate esters include trimethyl phosphate, triethyl phosphate, ethyl dimethyl phosphate, diethyl methyl phosphate, tripropyl phosphate, tributyl phosphate, tri(trifluoromethyl) phosphate, tri(trichloromethyl) phosphate, tri(trifluoroethyl) phosphate, 2-ethoxy-1,3,2-dioxaphospholan-2-one, 2-trifluoroethoxy-1,3,2-dioxaphospholan-2-one, and 2-methoxyethoxy-1,3,2-dioxaphospholan-2-one.
[0102] Examples of the nitrile compound include acetonitrile, etc. Examples of the amide compound include DMF, etc. Examples of the sulfone include dimethyl sulfone and diethyl sulfone, etc.
[0103] These solvents may be used alone or in combination of two or more.
[0104] The concentration of the electrolyte in the electrolytic solution is preferably 1.2 to 5.0 mol / L, more preferably 1.5 to 4.5 mol / L, further preferably 1.8 to 4.0 mol / L, and particularly preferably 2.0 to 3.5 mol / L. Such an electrolyte has an appropriate viscosity and can form a liquid film between the coated electrode active material particles, thereby imparting a lubricating effect (position adjustment ability of the coated electrode active material particles) to the coated electrode active material particles.
[0105] (electrode active material layer) In the lithium ion battery electrode of the present invention, the thickness of the electrode active material layer is preferably 150 to 600 μm, and more preferably 200 to 450 μm, from the viewpoint of battery performance.
[0106] (current collector) Examples of materials constituting the current collector include metal materials such as copper, aluminum, titanium, stainless steel, nickel, and alloys thereof, as well as baked carbon, conductive polymer materials, conductive glass, and the like. The shape of the current collector is not particularly limited, and may be a sheet-like current collector made of the above-mentioned material, or a deposition layer made of fine particles made of the above-mentioned material. The thickness of the current collector is not particularly limited, but is preferably 50 to 500 μm.
[0107] The current collector may be a resin current collector.
[0108] As the conductive polymer material constituting the resin collector, for example, a resin to which a conductive agent has been added can be used. As the conductive agent constituting the conductive polymer material, the same conductive filler as that in the coating layer can be suitably used. Examples of resins that constitute the conductive polymer material include polyethylene (PE), polypropylene (PP), polymethylpentene (PMP), polycycloolefin (PCO), polyethylene terephthalate (PET), polyethernitrile (PEN), polytetrafluoroethylene (PTFE), styrene-butadiene rubber (SBR), polyacrylonitrile (PAN), polymethyl acrylate (PMA), polymethyl methacrylate (PMMA), polyvinylidene fluoride (PVdF), epoxy resin, silicone resin, and mixtures thereof.
[0109] From the viewpoint of electrical stability, polyethylene (PE), polypropylene (PP), polymethylpentene (PMP) and polycycloolefin (PCO) are preferred, and polyethylene (PE), polypropylene (PP) and polymethylpentene (PMP) are more preferred. The resin current collector can be obtained by a known method described in JP-A-2012-150905 and JP-A-2015 / 005116.
[0110] (Method of manufacturing electrodes for lithium-ion batteries) The lithium ion battery electrode of the present invention can be produced, for example, by applying an electrode slurry containing coated electrode active material particles, a conductive assistant, and an electrolyte to a current collector and then drying the electrode to produce a lithium ion battery electrode having an electrode active material layer on a current collector. Specifically, the electrode slurry is applied onto a current collector using a coating device such as a bar coater, and then a nonwoven fabric is placed on the active material to absorb the liquid, thereby removing the solvent, and if necessary, the resulting mixture is pressed with a press.
[0111] <Lithium-ion battery> The lithium ion battery of the present invention comprises the lithium ion battery electrode of the present invention.
[0112] A lithium ion battery can be obtained by combining the lithium ion battery electrode of the present invention with a counter electrode, housing it together with a separator in a cell container, injecting an electrolyte, and sealing the cell container. Alternatively, a lithium ion battery can be obtained by forming the above-mentioned positive electrode for a lithium ion battery on one side of a current collector and a negative electrode on the other side to produce a bipolar electrode, stacking the bipolar electrode with a separator and storing it in a cell container, injecting an electrolyte, and sealing the cell container. The lithium ion battery of the present invention preferably comprises the lithium ion battery electrode of the present invention in both the positive electrode and the negative electrode.
[0113] Examples of the separator include known separators for lithium ion batteries, such as porous films made of polyethylene or polypropylene, laminated films of porous polyethylene film and porous polypropylene, nonwoven fabrics made of synthetic fibers (polyester fibers, aramid fibers, etc.) or glass fibers, and those having ceramic particles such as silica, alumina, titania, etc. attached to their surfaces.
[0114] The present specification describes the following inventions: [1] A coated electrode active material particle for a lithium ion battery, comprising an electrode active material particle for a lithium ion battery, at least a part of the surface of which is coated with a coating layer containing a polymer compound, a conductive filler, and an organic solvent, wherein the weight ratio of the organic solvent contained in the coating layer is 10 to 1000 ppm based on the weight of the coated electrode active material particle for a lithium ion battery. [2] The coated electrode active material particles for lithium ion batteries according to [1] above, wherein the organic solvent is at least one selected from the group consisting of acetone, toluene, isopropyl alcohol, ethyl acetate, N,N-dimethylformamide and N-methyl-2-pyrrolidone. [3] A lithium ion battery electrode comprising a non-bound body containing the coated electrode active material particles for lithium ion batteries according to [1] or [2] above and a conductive assistant. [4] A lithium ion battery comprising the lithium ion battery electrode according to [3] above. EXAMPLES
[0115] The present invention will now be described in detail with reference to examples, but the present invention is not limited to these examples as long as they do not deviate from the gist of the present invention. In addition, unless otherwise specified, parts means parts by weight and % means % by weight.
[0116] [Preparation of electrolyte] An electrolyte was prepared by dissolving LiN(FSO2)2 at a ratio of 2.0 mol / L in a mixed solvent of ethylene carbonate (EC) and propylene carbonate (PC) (volume ratio 1:1).
[0117] [Preparation of resin collector] A resin mixture was obtained by melt-kneading 70 parts of polypropylene [product name "SunAllomer PL500A", manufactured by SunAllomer Co., Ltd.], 25 parts of carbon nanotubes [product name "FloTube9000", manufactured by CNano Corporation], and 5 parts of a dispersant [product name "UMEX 1001", manufactured by Sanyo Chemical Industries, Ltd.] in a twin-screw extruder at 200°C and 200 rpm. The obtained resin mixture was passed through a T-die extrusion film molding machine and stretched and rolled to obtain a conductive film for resin current collector with a thickness of 100 μm. Next, the obtained conductive film for resin current collector was cut into a circle with a diameter of 15 mm or 16 mm, and nickel was vapor-deposited on one side, followed by connecting a terminal (5 mm × 3 cm) for taking out current to obtain a resin current collector. A circular resin current collector having a diameter of 15 mm was used as the positive electrode resin current collector, and a circular resin current collector having a diameter of 16 mm was used as the negative electrode resin current collector.
[0118] Comparative Example 1 [Preparation of Coating Layer Composition] A four-neck flask equipped with a stirrer, a thermometer, a reflux condenser, a dropping funnel and a nitrogen gas inlet tube was charged with 150 parts of DMF and heated to 75°C. Next, a monomer composition containing 91 parts of acrylic acid, 9 parts of methyl methacrylate and 50 parts of DMF, and an initiator solution containing 0.3 parts of 2,2'-azobis(2,4-dimethylvaleronitrile) and 0.8 parts of 2,2'-azobis(2-methylbutyronitrile) dissolved in 30 parts of DMF were continuously dropped into the four-neck flask with nitrogen over a period of 2 hours while stirring, to carry out radical polymerization. After the dropwise addition was completed, the reaction was continued at 75°C for 3 hours. The temperature was then raised to 80°C and the reaction was continued for 3 hours to obtain a copolymer solution with a resin concentration of 30%. The obtained copolymer solution was dropped into acetone under stirring to perform purification. After purification, the copolymer solution was transferred to a Teflon (registered trademark) vat and dried under reduced pressure at 150°C and 0.01 MPa for 3 hours, and DMF and acetone were distilled off to obtain a polymer compound. The obtained polymer compound was roughly crushed with a hammer, and then further crushed in a mortar to obtain a powdered polymer compound. One part of the polymer compound was dissolved in 3 parts of DMF, and acrylic acid:methyl methacrylate (weight ratio 91:9) was added so that the monomer content was 0.1 mol% based on the number of moles of the polymer compound, to obtain a coating layer composition.
[0119] [Preparation of coated positive electrode active material particles] Cathode active material particles (LiNi 0.8 Co 0.15Al 0.05 90.12 parts of O2 powder (volume average particle diameter: 4 μm) was placed in a universal mixer, high-speed mixer FS25 [manufactured by EarthTechnica Corporation], and while stirring at room temperature and 720 rpm, 12.56 parts of the coating layer composition was added dropwise over 2 minutes, and the mixture was further stirred for 5 minutes. Next, 3.14 parts of acetylene black (Denka Black (registered trademark) manufactured by Denka Co., Ltd.), which is a conductive additive, and ceramic particles (AEROSIL 200 (silicon dioxide, BET specific surface area 200 m) 2 / g, product name "AEROSIL 200", manufactured by Nippon Aerosil Co., Ltd.) ) 2.10 parts of the mixture was added in portions over a period of 2 minutes, and stirring was continued for 30 minutes. Thereafter, the pressure was reduced to 0.01 MPa while continuing stirring, and then the temperature was raised to 140° C. while continuing stirring and reducing pressure, and the stirring, reducing pressure and temperature were maintained for 13 hours to distill off the volatile matter. The obtained powder was classified using a sieve with 200 μm openings to obtain coated positive electrode active material particles of Comparative Example 1.
[0120] The weight percentage of the organic solvent contained in the obtained coated positive electrode active material particles was measured using a GC measuring device (Gas Chromatograph GC-2010 [manufactured by Shimadzu Corporation]), and the weight percentage of the organic solvent was calculated in ppm order from the area ratio of the peak intensities.
[0121] (Examples 1 to 5, Comparative Example 2) Thereafter, an organic solvent (DMF) was added so that the weight ratio of the organic solvent contained in the coated positive electrode active material particles became the weight ratio shown in Table 1, and the mixture was stirred at room temperature and 720 rpm for 5 minutes using a universal mixer high-speed mixer FS25 to obtain the coated positive electrode active material particles of Examples 1 to 5 and Comparative Example 2, respectively.
[0122] [Table 1]
[0123] [Preparation of positive electrodes for lithium-ion batteries] 98.50 parts of the prepared coated positive electrode active material particles, 2.06 parts of carbon fiber [Dona Carbo Milled S-243, manufactured by Osaka Gas Chemicals Co., Ltd.: average fiber length 500 μm, average fiber diameter 13 μm: electrical conductivity 200 mS / cm], and 1.03 parts of Ketjen black [EC300J, manufactured by Lion Specialty Chemicals Co., Ltd.] were mixed to prepare a positive electrode slurry. The prepared positive electrode slurry was applied to a die with a diameter of 15 mm so that the amount of the positive electrode active material particles was 50 mg / cm 2 The mixture was filled to a density of 1 ton / cm using a press (HANDTAB-100T15, manufactured by Ichihashi Seiki Co., Ltd.). 2 The positive electrode active material layer (thickness: 213 μm) was formed by tableting at a pressure of 1000 μm, and the positive electrode active material layer (thickness: 213 μm) was laminated on one side of the above-mentioned resin current collector to prepare positive electrodes for lithium ion batteries (circular shape with a diameter of 15 mm) according to Examples 1 to 5 and Comparative Examples 1 and 2.
[0124] The electrode strength (flexibility) of the obtained positive electrode for a lithium ion battery was measured as follows. The yield stress of the obtained positive electrode for lithium ion batteries (sample size: circle with a diameter of 15 mm) was measured using an autograph (manufactured by Shimadzu Corporation) in accordance with ISO178 (Plastics - Determination of bending properties), and the electrode strength was evaluated according to the following criteria. First, each sample of the lithium-ion battery positive electrode was set on a jig with a support distance of 5 mm, and a load cell (rated load: 20 N) set on an autograph was lowered toward the electrode at a rate of 1 mm / min. The distance (mm) that the load cell fell from when it touched the electrode to the yield point was calculated as the yield point stroke. The longer the stroke, the more flexible the electrode is. The measurement results are shown in Table 2.
[0125] [Table 2]
[0126] From Table 2, it was confirmed that the positive electrodes for lithium ion batteries of Examples 1 to 5 using coated positive electrode active material particles in which the coating layer contained a predetermined organic solvent had sufficient electrode flexibility.
[0127] Comparative Example 2 [Preparation of coating layer composition for first coating layer] In the same manner as in Comparative Example 1, a coating layer composition for a first coating layer was obtained.
[0128] [Preparation of coating layer composition for second coating layer] In a four-neck flask equipped with a stirrer, a thermometer, a reflux condenser, a dropping funnel, and a nitrogen gas inlet tube, 30 parts of n-butyl acrylate, 20 parts of 2-hydroxyethyl acrylate, 50 parts of acrylonitrile, and 390 parts of toluene were charged and heated to 75° C. 10 parts of toluene, 0.200 parts of 2,2'-azobis(2,4-dimethylvaleronitrile), and 0.200 parts of 2,2'-azobis(2-methylbutyronitrile) were mixed. While blowing nitrogen into the flask, the resulting monomer mixture was continuously added dropwise to the polymerization initiator using a dropping funnel over a period of 4 hours to carry out radical polymerization. After the dropping was completed, a solution of 0.800 parts of 2,2'-azobis(2,4-dimethylvaleronitrile) dissolved in 12.4 parts of toluene was continuously added using a dropping funnel over the period of 6 to 8 hours after the start of polymerization. The polymerization was further continued for 2 hours, and 488 parts of toluene was added to obtain a coating layer composition for a second coating layer having a resin concentration of 10% by weight.
[0129] [Preparation of coated negative electrode active material particles] (Formation of the first coating layer) 77.3 parts of negative electrode active material particles (hard carbon powder, volume average particle diameter 25 μm) were placed in a universal mixer, high-speed mixer FS25 [manufactured by EarthTechnica Corporation], and while stirring at room temperature and 720 rpm, 21.2 parts of the coating layer composition for the first coating layer (5.3 parts in terms of solid content) was added dropwise over 2 minutes, and the mixture was further stirred for 5 minutes. Next, while stirring, 5.3 parts of graphite (UP) [flaky graphite, volume average particle size: 4.5 μm] serving as a conductive additive was added in portions over a period of 2 minutes, and stirring was continued for 30 minutes.
[0130] (Formation of second coating layer) Further, while stirring, 59.0 parts of the coating composition for the second coating layer at 40°C (5.9 parts in terms of solid content) was added by spraying over 2 minutes using a spray system using a nozzle of WA-101-102P (manufactured by Anest Iwata Corporation) (spray rate 100 ml / min), and further stirred for 5 minutes. Next, while stirring, 4.0 parts of acetylene black (AB) [manufactured by Denka Co., Ltd., product name "Denka Black", volume average particle size 35 nm], which is a conductive assistant, was added in portions over 2 minutes, and stirring was continued for 30 minutes. Thereafter, the pressure was reduced to 0.01 MPa while continuing stirring, and then the temperature was raised to 140° C. while continuing stirring and reducing pressure, and the stirring, reducing pressure and temperature were maintained for 13 hours to distill off the volatile matter. The obtained powder was classified using a sieve with 200 μm openings to obtain coated negative electrode active material particles.
[0131] The weight percentage of the organic solvent contained in the obtained coated negative electrode active material particles was measured using a GC measuring device (Gas Chromatograph GC-2010 [manufactured by Shimadzu Corporation]), and the weight percentage of the organic solvent was calculated in ppm order from the area ratio of the peak intensities.
[0132] (Examples 6 to 10, Comparative Examples 3 and 4) Then, an organic solvent (DMF:toluene = 1:1) was added so that the weight ratio of the organic solvent contained in the coated negative electrode active material particles was the weight ratio listed in Table 3, and the mixture was stirred at room temperature and 720 rpm for 5 minutes using a universal mixer high-speed mixer FS25 to obtain the coated negative electrode active material particles of Examples 6 to 10, respectively.
[0133] [Table 3]
[0134] (Preparation of negative electrodes for lithium-ion batteries) 99 parts of the prepared coated negative electrode active material particles and 1 part of carbon fiber [DonaCarbo Milled S-243, manufactured by Osaka Gas Chemicals Co., Ltd.: average fiber length 500 μm, average fiber diameter 13 μm: electrical conductivity 200 mS / cm] were mixed to prepare a negative electrode slurry. The negative electrode slurry thus prepared was applied to a die having a diameter of 16 mm so that the weight of the negative electrode active material particles was 23.4 mg / cm 2 The mixture was filled to a density of 1 ton / cm using a press (HANDTAB-100T15, manufactured by Ichihashi Seiki Co., Ltd.). 2 The negative electrode active material layer (thickness: 300 μm) was formed by tableting at a pressure of 1000 μm, and laminated on one side of the resin current collector to prepare negative electrodes for lithium ion batteries (circular shape with a diameter of 16 mm) according to Examples 6 to 10 and Comparative Examples 3 and 4, respectively.
[0135] The electrode strength (flexibility) of the obtained negative electrode for a lithium ion battery was measured in the same manner as the positive electrode for a lithium ion battery. The measurement results are shown in Table 4.
[0136] [Table 4]
[0137] From Table 4, it was confirmed that the lithium ion battery negative electrodes of Examples 6 to 10, which used coated negative electrode active material particles in which the coating layer contained a predetermined organic solvent, had sufficient electrode flexibility.
[0138] [Making a lithium-ion battery] A lithium ion battery was produced by combining a lithium ion battery positive electrode and a lithium ion battery negative electrode shown in Table 2 or Table 4 with a separator (Celgard #3501) interposed therebetween as shown in Table 5 and injecting an electrolyte solution.
[0139] <Measurement of internal resistance increase rate> The lithium-ion batteries were evaluated at 25°C using a charge / discharge measuring device "HJ-SD8" [manufactured by Hokuto Denko Corporation] according to the following method. The battery was charged to 4.2 V using a constant current constant voltage method (0.1 C), then rested for 10 minutes, and discharged to 2.5 V using a constant current method (0.1 C). Using the constant current constant voltage method (also called CCCV mode), the voltage and current were measured 0 seconds after discharge at 0.1 C and 10 seconds after discharge at 0.1 C, and the internal resistance was calculated using the following formula. The smaller the internal resistance, the better the battery characteristics. The voltage 0 seconds after discharging is the voltage measured immediately after discharging (also called the discharge voltage). [Internal resistance (Ω cm 2 )] = [(Voltage 0 seconds after discharge at 0.1 C) - (Voltage 10 seconds after discharge at 0.1 C)] ÷ [(Current 0 seconds after discharge at 0.1 C) - (Current 10 seconds after discharge at 0.1 C)] × [Facing area of electrodes (cm 2 )] To measure the internal resistance, a repeated test of 20 cycles was conducted, and the internal resistance at the second cycle (initial internal resistance) was compared with the internal resistance at the 20th cycle (internal resistance at the 20th cycle / internal resistance at the second cycle) to calculate the "internal resistance increase rate (%)."
[0140] <Capacity retention rate measurement> A charge / discharge test was performed on the lithium ion battery at 25° C. using a charge / discharge measuring device “HJ-SD8” [manufactured by Hokuto Denko Corporation] according to the following method. The battery was charged to 4.2 V using a constant current / constant voltage method (0.1 C), then after a 10-minute rest, it was discharged to 2.5 V using a constant current method (0.1 C). The discharged capacity at this time was defined as [discharge capacity (mAh)]. A repeated test of 20 cycles was carried out, and the 20 cycle capacity retention rate (%) was calculated.
[0141] [Table 5]
[0142] From Table 5, it was confirmed that in a lithium ion battery having a positive electrode and a negative electrode made of lithium ion battery electrodes prepared using the coated electrode active material particles of the embodiment, an increase in internal resistance value can be suppressed and the capacity retention rate is excellent. [Industrial Applicability]
[0143] The coated electrode active material particles of the present invention are particularly useful as electrode active material particles for lithium ion batteries and the like used in stationary power sources, mobile phones, personal computers, hybrid automobiles, electric automobiles, and the like.
Claims
1. A coated electrode active material particle for a lithium ion battery, comprising: at least a part of a surface of an electrode active material particle for a lithium ion battery coated with a coating layer containing a polymer compound, a conductive filler, and an organic solvent; The coated electrode active material particles for lithium ion batteries have an organic solvent contained in the coating layer in a weight ratio of 10 to 1000 ppm based on the weight of the coated electrode active material particles for lithium ion batteries.
2. 2. The coated electrode active material particles for lithium ion batteries according to claim 1, wherein the organic solvent is at least one selected from the group consisting of acetone, toluene, isopropyl alcohol, ethyl acetate, N,N-dimethylformamide and N-methyl-2-pyrrolidone.
3. 3. A lithium ion battery electrode comprising a non-bound body containing the coated electrode active material particles for lithium ion batteries according to claim 1 or 2 and a conductive assistant.
4. A lithium ion battery comprising the lithium ion battery electrode according to claim 3.
Citation Information
Patent Citations
Resin composition for coating nonaqueous secondary battery active material and coated active material for nonaqueous secondary battery
JP2017160294A
